Temas controversos em unidades de ensino potencialmente significativa (UEPS) : um estudo acerca das concepções dos bolsistas do PIBID/Física - Andrade, Caroline de Oliveira (2021)
The research seeks to present understandings about the insertion of the Controversial Theme in the educational product of the Potentially Significant Teaching Unit. Although recent, Controversial Themes can be used to discuss different themes in the school environment. In verifying this concept, this methodological alternative enables students to promote moral, ethical and political reasoning in determining the positive and negative aspects related to the contents of the Teaching of Physics, in addition to enabling Critical Meaningful Learning. Understanding that its use plays an important role in student education, the motivation for this research in relation to the correct use and conception of the Controversial Theme emerged within the discussions of the group of scholarship holders of the Institutional Program for Teaching Initiation Scholarships at the Federal University of Sergipe/Campus Prof. Alberto Carvalho, when realizing the possibility of Controversial Themes being addressed/inserted in the educational product that were produced by these future teachers. The research aimed to identify, from the educational product of the developed teaching units, discussions that involve a Controversial Theme, identifying the meanings that emerge from the interactions provided by the scholarship holders' texts, and analyze how these discussions influence the learning of Physics. This is a qualitative research in which, as a data collection instrument, analyzes of scientific works and semi-structured interviews were carried out in line with the collective interview. For analysis, the Discursive Textual Analysis was used as a theoretical and methodological support. The analytical process took place through the categorization for semi-structured interviews and collective interview carried out with the scholarship holders. From the analysis of scientific works, it was evident that the meanings attributed to the Controversial Theme are in the fact that they involve value judgments, whether of a political, religious, economic, social and environmental nature. It is also revealed that there is an appropriation of this conception by the interviewed scholarship holders and they reproduce ideas from scientific works related to its conception, contextualizing it according to their own arguments. Therefore, it is glimpsed that from this investigation, there is an appropriation of Controversial Themes, thus contributing to have even more improvements in the training process in Physics Education. Considering that its insertion is important, as it favors the formation of creative, reflective, critical and contextualized citizens about their own personal and professional actions.